2000
DOI: 10.2527/2000.7841067x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abomasal infusion of high levels of lysine or methionine, or both, on ruminal fermentation, eating behavior, and performance of lactating dairy cows.

Abstract: Four multiparous late-lactation Holstein cows were fed a basal ration designed to be co-limiting in intestinally absorbable supplies of methionine and lysine. Cows were supplemented with no amino acids, lysine by abomasal infusion to 140% of the calculated intestinally absorbable requirement, methionine by abomasal infusion to 140% of requirement, or both amino acids in a 4 x 4 Latin square design with 28-d periods. Unsupplemented cows consumed 23.8 kg/d of dry matter and produced 36.9 kg/d of milk containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 16 publications
7
40
1
Order By: Relevance
“…Indeed this hypothesis agrees with results of a study where the control ration had the lowest production, even with a calculated ratio close to 3.0, while positive production responses were seen for both Met and Lys supplementation, even when the supplementation changed the ratios to 1.3 and 4.6 respectively (Wang et al, 2010). Robinson et al (2000) reported that oversupplying both Met and Lys simultaneously changed partitioning of energy, with their combined infusion improving energetic efficiency of the cows without affecting general animal performance, thereby increasing the NE density of the ration to prevent a negative energy balance in the cows. This corresponds to our study where combined supplementation of Phe and Met changed the way energy was utilized vs. when Met was supplemented alone.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Indeed this hypothesis agrees with results of a study where the control ration had the lowest production, even with a calculated ratio close to 3.0, while positive production responses were seen for both Met and Lys supplementation, even when the supplementation changed the ratios to 1.3 and 4.6 respectively (Wang et al, 2010). Robinson et al (2000) reported that oversupplying both Met and Lys simultaneously changed partitioning of energy, with their combined infusion improving energetic efficiency of the cows without affecting general animal performance, thereby increasing the NE density of the ration to prevent a negative energy balance in the cows. This corresponds to our study where combined supplementation of Phe and Met changed the way energy was utilized vs. when Met was supplemented alone.…”
Section: Discussionsupporting
confidence: 81%
“…As the predicted Lys:Met ratios may not reflect the actual ratios, interpretation of the Lys:Met ratio concept in studies outside the NRC (2001) is difficult. In the study of Robinson et al (2000), creating an imbalance in the suggested optimum Lys:Met ratio by supplementing Lys (i.e., changing the ratio from 3.0 to 3.9) had no effect on production, but creating a theoretical imbalance by supplementing Met (i.e., changing the ratio from 3.0 to 2.3), reduced DM intake, milk production and lactose yields. While restoring the ratio to 3:1 by supplementing Lys and Met together did not impact production, the negative effects of high Met supplementation remained, even at the 3.0 Lys:Met ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AA reaching the duodenum in a common grass silage-based diet can be limiting in specific AA. Infusion of individual AA, as His (Vanhatalo et al, 1999), Met (Pisulewski et al, 1996;Robinson et al, 2000) and Lys (Robinson et al, 2000) has increased the milk protein production, which indicates that these AA have been limiting milk protein synthesis. Compared with in His limiting diets (Thivierge et al, 2002), the present plasma His concentrations were high, and combined with low extraction rates, this suggests that His was not limiting on the AP or AB treatments.…”
Section: Discussionmentioning
confidence: 99%